Privatization Trends - Kikeri, Sunita (World Bank, Washington, DC, 2012)
An update of the World Bank Group's Privatization Database shows that privatization in developing countries continued to pick up in 2004 and 2005, with 400 transactions worth US$90 billion. Apart from 1997, the 2005 result in nominal terms is the highest since 1990 (when the data start). Transaction values remained concentrated in 10 countries, with 4 new entrants joining the group. The top 10 deals, largely in banking and telecommunications, again accounted for 40 percent of the total.